2015
DOI: 10.1016/j.nimb.2015.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Swift heavy ion irradiation damage in Ti–6Al–4V and Ti–6Al–4V–1B: Study of the microstructure and mechanical properties

Abstract: Keywords:Swift heavy ion (SHI) irradiation damage Microstructure Mechanical properties Ti-6Al-4V Ti-6Al-4V-1B a b s t r a c t The a + b alloy Ti-6Al-4V (wt.%) and the boron-modified Ti-6Al-4V-1B (wt.%), due to their low activation, corrosion resistance, good mechanical properties, and their commercial availability, were chosen as candidate materials for the beam dump for the Facility for Rare Isotope Beams (FRIBs) at Michigan State University: a new generation accelerator with high power heavy ion beams. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The metallic foils are irradiated with ion of energies 500 keV, 600 keV and 1 MeV at different temperatures ranging from 20 to 573 K. They observed that grain boundary migration occurs by atomic jumps due to hitting of thermal spikes and biased by the local grain‐boundary curvature driving force. Amroussia et al 19 studied the effects of Ar ions at an energy of 36 MeV and Xe ions at 92 MeV on surfaces of Ti–6Al–4 V and Ti–6Al–4 V–1B samples. They found that no microstructural changes were observed before and after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The metallic foils are irradiated with ion of energies 500 keV, 600 keV and 1 MeV at different temperatures ranging from 20 to 573 K. They observed that grain boundary migration occurs by atomic jumps due to hitting of thermal spikes and biased by the local grain‐boundary curvature driving force. Amroussia et al 19 studied the effects of Ar ions at an energy of 36 MeV and Xe ions at 92 MeV on surfaces of Ti–6Al–4 V and Ti–6Al–4 V–1B samples. They found that no microstructural changes were observed before and after irradiation.…”
Section: Introductionmentioning
confidence: 99%